The impact of short-term intensive fasting on physical health and gut microbiota in obese individuals - Feng Ji; Shiya Wang; Li Wang; Yixuan Zhao; Jiabin Zhong; Ruohan Wang; Jianing Qu; Yunhang Lu; Na Yuan; Qing Zhang (Frontiers in Nutrition, 2026)
Objectives This study aimed to characterize how a 7-day complete water-only fast followed by structured refeeding was associated with changes in body weight, hydration-dependent bioelectrical-impedance estimates, physical test performance, cardiovascular indicators, and gut microbial ecology in adults with obesity and normal-weight controls. Methods Seventy-two eligible volunteers formed prespecified BMI sampling strata (normal weight, n = 36; obesity, n = 36), from which 14 participants were randomly selected within each stratum before the intervention and before outcome collection ( N = 28). All selected participants completed a supervised 7-day water-only fast followed by a 7-day structured refeeding period. Physical indicators were assessed pre-fasting, post-fasting, and post-refeeding and analyzed using two-factor mixed-design repeated-measures models; gut microbiota (16S rRNA) was profiled pre- and post-fasting. Results BMI-group-by-time interactions were significant for body weight and BMI (both p < 0.001) but not for BIA-derived fat mass, body-fat percentage, or muscle mass (all p > 0.05). Dynamometer-recorded grip, knee-flexion, and knee-extension scores increased over time (all time-effect p < 0.001), but none showed a BMI-group-by-time interaction (all p ≥ 0.340). Gut microbial alpha diversity remained largely stable apart from an FDR-significant ACE-index reduction in the normal-weight group ( q = 0.021); most taxonomic findings did not survive FDR correction, and beta-diversity analysis showed no community-level convergence between groups. Conclusion Supervised seven-day water-only fasting followed by structured refeeding was associated with reduced body weight, particularly in participants with obesity. Changes in body composition were BIA-derived estimates, while higher dynamometer scores represented measured test performance that may have been influenced by familiarization. Gut-microbiota alpha diversity was largely stable, with exploratory compositional changes supporting further investigation in controlled studies.